Achieving Hemostasis Posttranscatheter Aortic Valve Replacement in a Patient with Aortobifemoral Bypass Graft Using Perclose Device: A Novel Technique - Ebubechukwu Ezeh; Mohammad Amro; Esiemoghie Akhigbe; Mackenzie Hamilton; Mehrette Maru (Case Reports in Cardiology)
The presence of aortobifemoral bypass graft can complicate vascular access during percutaneous intervention. Choosing an access route for transcatheter aortic valve replacement (TAVR) in this patient population can be challenging. Access options are further limited by the presence of coexisting vascular comorbidities such as extensive peripheral artery diseases in these patients. Adequate preoperative planning to determine the suitability of different access sites is, therefore, very crucial. Our case report shows that the use of Perclose can be a viable option for achieving hemostasis after a direct puncture of an aortobifemoral bypass graft during transfemoral TAVR.